Finding trafficked children through crowdsourcing: a usability evaluation - Goh, Dion Hoe-Lian (2022)
Purpose: The purpose of this paper is to investigate how perceived usability and user characteristics influence the intention to use a crowdsourcing application for finding potentially trafficked children. As part of this effort, the authors also attempt to uncover the usability concerns surrounding the use of this application. Design/methodology/approach: The authors first describe Zhongxun, which is the application used in the present paper. Next, they conducted a survey eliciting usability perceptions of Zhongxun. A total of 287 participants were recruited for the survey which used constructs adapted from the Computer System Usability Questionnaire as well as various demographic variables. Hierarchical regression analysis was used to ascertain factors influencing intention to use Zhongxun. Participants' qualitative feedback was also analyzed to derive themes pertaining to areas of improvement. Findings: The results showed that system usefulness was the factor that most positively influenced intention to use Zhongxun, followed by information quality and interface quality. Interestingly, a higher level of education was negatively associated with intention to use the application. Qualitative feedback suggested various ways of improving Zhongxun's functionality. Participants recommended the incorporation of gamification mechanisms as a new feature of the application. Cultivating awareness of Zhongxun was also suggested as a means to attract new users. Practical implications: The work can help inform the design of crowdsourcing applications for finding missing and potentially trafficked children, as well as similar systems. Implications include the need for simplicity of design, communication strategies to attract new and retain existing users, and instilling confidence in the quality of crowdsourced contributions. Originality/value: Prior research in evaluating the usability of crowdsourcing applications has been performed but not in the context of finding missing and potentially trafficked children. The task of finding such children is markedly different from previous usage contexts and could impact perceptions of usability and usefulness. Hence, the present study attempts to plug this research gap.